Chronic oral administration of pine bark extract (flavangenol) attenuates brain and liver mRNA expressions of HSPs in heat-exposed chicks. (August 2016) - Yang, Hui; Chowdhury, Vishwajit S.; Bahry, Mohammad A.; Tran, Phuong V.; Do, Phong H.; Han, Guofeng; Zhang, Rong; Tagashira, Hideki; Tsubata, Masahito; Furuse, Mitsuhiro
Abstract: Exposure to a high ambient temperature (HT) can cause heat stress, which has a huge negative impact on physiological functions. Cellular heat-shock response is activated upon exposure to HT for cellular maintenance and adaptation. In addition, antioxidants are used to support physiological functions under HT in a variety of organisms. Flavangenol, an extract of pine bark, is one of the most potent antioxidants with its complex mixture of polyphenols. In the current study, chronic (a single daily oral administration for 14 days) or acute (a single oral administration) oral administration of flavangenol was performed on chicks. Then the chicks were exposed to an acute HT (40±1 °C for 3 h) to examine the effect of flavangenol on the mRNA expression of heat-shock protein (HSP) in the brain and liver. Rectal temperature, plasma aspartate aminotransferase (AAT), a marker of liver damage, and plasma corticosterone as well as metabolites were also determined. HSP-70 and -90 mRNA expression, rectal temperature, plasma AAT and corticosterone were increased by HT. Interestingly, the chronic, but not the acute, administration of flavangenol caused a declining in the diencephalic mRNA expression of HSP-70 and -90 and plasma AAT in HT-exposed chicks. Moreover, the hepatic mRNA expression of HSP-90 was also significantly decreased by chronic oral administration of flavangenol in HT chicks. These results indicate that chronic, but not acute, oral administration of flavangenol attenuates HSP mRNA expression in the central and peripheral tissues due to its possible role in improving cellular protective functions during heat stress. The flavangenol-dependent decline in plasma AAT further suggests that liver damage induced by heat stress was minimized by flavangenol. Highlights: Flavangenol attenuated the heat stress-induced HSPs mRNA expression in chicks. Heat stress-induced high plasma AAT concentration was minimized by flavangenol. Flavangenol would be beneficial against heat stress induced cellular damage.